which form you choose for ypur business project in Bahrain - Gumed, Prof. Salem A. (IJRDO - Journal of Social Science and Humanities Research, 2019)
Business enterprises vary from simple structure as sole-man operation to complicated huge organizations. The simplest type of enterprises can be formed in what so called sole owner company which consists of one person, who provides capital and assumes risks of the project. However, it is obvious that most projects, in the present time, need a huge capital, good management, experiments and skillful labor power which cannot be provided only through companies as they are the most appropriate instrument to gather all these utilities.Although companies, in theory, are economical organizations enjoy legal personality, they are different types. Each differs from others in certain features, so, promoters and investors, while incorporating their projects should be aware of the structure of different types of companies.Companies in Bahrain, but the Sole owner company, are constituted by contracts. They, save joint venture, enjoy legal personality. The relative importance of these two aspects varies from a company to another.The aim of this paper is to explore the various forms of business projects that can be chosen for business enterprises in Kingdom of Bahrain, their characteristics, advantages and disadvantages of each form in order to facilitate the idea enabling promotors and investors to choose the most appropriate form for their own projects.